Gambaran Sistem Pengelolaan Rekam Medis di Ruang Rawat Inap Rumah Sakit Harum Sisma Medika Tahun 2017 - Fransisko HK; Diana Barsasella (Jurnal Persada Husada Indonesia, 2017)
Medical records are a permanent legal document that should contain sufficient information to identify patients, justify diagnosis and treatment and record the results. But because the documentation in the medical records is done by various health care providers such as doctors, nurses, therapists and so on and because it is done as a second activity after providing patient care, the documentation is not always as complete and exact as needed or desirable. The purpose of this research is to know the description of Medical Record Management System in the Inpatient Room of Harum Sisma Medika Hospital in 2017 with a sample of 73 people and data collected using questionnaire. Descriptive research design to see the description of research. From the research, there were 64 (87.7%) respondents stated good about medical record system, 58 (79.5%) stated good about medical record method, 52 (71.2%) stated good about medical record processing, 46 (63.0%) respondents Stated good about medical record analysis, 49 (67.1%) of respondents stated good about record medical record system and 67 (91.8%) respondents stated good about quality management of medical record. Therefore, it is expected that all officers can continuously improve the medical record management system in the Inpatient Room of Harum Sisma Medika Hospital.